2010
DOI: 10.1016/j.jada.2010.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents Demonstrate Improvement in Obesity Risk Behaviors after Completion of Choice, Control & Change, a Curriculum Addressing Personal Agency and Autonomous Motivation

Abstract: Background The rapid increase of obesity and diabetes risk beginning in youth, particularly those from disadvantaged communities, calls for prevention efforts. Objective To examine the impact of a curriculum intervention, Choice, Control, and Change (C3), on the adoption of the energy balance related behaviors of decreasing sweetened drinks, packaged snacks, fast food, and leisure screen time, and increasing water, fruits and vegetables, and physical activity, and on potential psychosocial mediators of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
219
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(226 citation statements)
references
References 49 publications
3
219
1
3
Order By: Relevance
“…Motivation is a strong predictor of weight reduction in children and adolescents in WRPs 13 . Previous school-based interventions demonstrated that youth who participate in enjoyable and engaging activities to enhance autonomous motivation experience more positive results in body mass index (BMI), healthy diet, and physical activity 10,14,15 . Few studies have evaluated autonomous motivation for physical activity and dietary intakes in school-age (particularly secondary school) students, but their fi ndings are appropriate for Western contexts 14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Motivation is a strong predictor of weight reduction in children and adolescents in WRPs 13 . Previous school-based interventions demonstrated that youth who participate in enjoyable and engaging activities to enhance autonomous motivation experience more positive results in body mass index (BMI), healthy diet, and physical activity 10,14,15 . Few studies have evaluated autonomous motivation for physical activity and dietary intakes in school-age (particularly secondary school) students, but their fi ndings are appropriate for Western contexts 14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…These results compare favorably to studies of adolescent obesity prevention interventions of longer duration using computer tailoring and goal setting (Contento, et al, 2010;Singh, Chin A Paw, Brug, & van Mechelen, 2007;Singh, et al, 2009;Singh, et al, 2006) as behavioral strategies. A recent meta-analysis found that goal setting was one of two promising intervention components to modify dietary fat, fruit and vegetable intake (Ammerman, Lindquist, Lohr, & Hersey, 2002).…”
Section: Discussionmentioning
confidence: 63%
“…For youth, a literature review found only one study investigating the effectiveness of a goal-setting characteristic (Shilts, et al, 2004a;White, & Skinner, 1988). More recently, three goal setting intervention effectiveness studies (Contento, Koch, Lee, & Calabrese-Barton, 2010;Patrick, et al, 2006;Singh, Chin A Paw, Brug, & van Mechelen, 2009) and a goal-setting effectiveness study were reported in the literature with each showing positive results (Shilts, Townsend, & Dishman, In Press).…”
Section: Introductionmentioning
confidence: 99%
“…(15) Applications include designing interventions to increase outcome expectations related to physical activity (16)(17) and home exercise adherence. (18) Other studies have applied outcome expectation and expectancy constructs to improve participation in longitudinal studies (19) and exercise adoption among an at-risk population.…”
Section: Methods Participantsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Nearly half of the massage therapists practiced alone (45.7%), while 15.9% practiced with a chiropractor, 14.6% practiced in a salon or spa, 12.6% practiced with other massage therapists, and 12% worked in other practice settings.…”
Section: Participant Characteristicsmentioning
confidence: 99%